2022
DOI: 10.31223/x5jw6m
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistent influence of precession on northern ice sheet variability since the early Pleistocene

Abstract: Before ~1M years ago, variations in global ice volume were dominated by changes in obliquity but the role of precession remains unresolved. Using a record of North Atlantic ice rafting spanning the last 1.7Myr, we find that the onset of ice rafting within a given glacial cycle (reflecting ice sheet expansion) consistently occurred during times of decreasing obliquity, while mass ice wasting (ablation) events were consistently tied to minima in precession. Furthermore, our results suggest that the ubiquitous as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
2
1
Order By: Relevance
“…We show that the precession forcing plays an important role in driving the glacial cycles before the MPT: (1) the precession forcing determines the timing of the threshold for deglaciation, while obliquity also supports the deglaciations of the 41-kyr glacial cycles; (2) the lead-lag relationship between precession and obliquity forcings determines the length of the interglacials and the shape of the glacial cycles; and (3) a thin and extensive North American ice sheet forms and retreats within one precession cycle when eccentricity is su ciently large. These ndings quantitatively support the recent discussions suggesting the importance of precession forcing on climate variabilities during the EP 18, [23][24][25]29 . The variations in the SH ice sheet may help to completely weaken signals from the ~ 20 kyr periodicity of precession forcing from sea-level records during the EP 21,22 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We show that the precession forcing plays an important role in driving the glacial cycles before the MPT: (1) the precession forcing determines the timing of the threshold for deglaciation, while obliquity also supports the deglaciations of the 41-kyr glacial cycles; (2) the lead-lag relationship between precession and obliquity forcings determines the length of the interglacials and the shape of the glacial cycles; and (3) a thin and extensive North American ice sheet forms and retreats within one precession cycle when eccentricity is su ciently large. These ndings quantitatively support the recent discussions suggesting the importance of precession forcing on climate variabilities during the EP 18, [23][24][25]29 . The variations in the SH ice sheet may help to completely weaken signals from the ~ 20 kyr periodicity of precession forcing from sea-level records during the EP 21,22 .…”
Section: Discussionsupporting
confidence: 89%
“…The existence of asymmetry has also been inferred for the pre-MPT periods based on statistical analyses 4,[26][27][28] . Recently, using records of North Atlantic ice rafting and δ 18 O records, it has been shown that deglaciations occur at minima in climatic precession during the EP 29 . However, the contribution of obliquity and precession forcings in determining the timings of terminations of the 41-kyr glacial cycles and the duration of interglacials has not been quantitatively elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…2a) and the absence of the internal oscillations in IcIES-MIROC (Watanabe et al, 2023). Nevertheless, our results with CLIMBER-2 do not contradict the observed influences of both climatic precession and obliquity forcing on the early Pleistocene 41-kyr glacial cycles (Liautaud et al, 2020;Barker et al, 2022;Watanabe et al, 2023). Indeed, the simulated sequence of glacial cycles and its spectra are close to those of the δ 18 O record if the amplitude of the climatic precession is realistic (Figs S11 and S12).…”
contrasting
confidence: 52%
“…There is general agreement that the glacial cycles are in some way paced by changes in the incoming solar radiation (i.e., insolation) caused by long-term variations of astronomical parameters (Hays et al, 1976;Huybers, 2011;Cheng et al, 2016;Tzedakis et al, 2017;Liautaud et al, 2020;Barker et al, 2022); (i) the obliquity ε (Fig. 1a) describes the Earth's axial 2 tilt and has a dominant periodicity around 41 kyr (Laskar et al, 2004), (ii) the eccentricity e of the orbit (Fig.…”
mentioning
confidence: 98%
“…There is general agreement that the glacial cycles are in some way paced by changes in the incoming solar radiation (i.e., insolation) caused by long-term variations of astronomical parameters (Hays et al, 1976;Huybers, 2011;Cheng et al, 2016;Tzedakis et al, 2017;Liautaud et al, 2020;Barker et al, 2022); (i) the obliquity ε (Fig. 1a) describes the Earth's axial tilt and has a dominant periodicity around 41 kyr (Laskar et al, 2004), (ii) the eccentricity e of the orbit (Fig.…”
Section: Introductionmentioning
confidence: 97%